Usefulness of colonoscopic examination with indigo carmine in diagnosing microscopic colitis - Suzuki, G.; Mellander, M. R.; Suzuki, A.; Rubio, C. A.; Lambert, R.; Björk, J.; Schmidt, P. T. (Endoscopy, 2011)
Microscopic colitis, comprising collagenous colitis and lymphocytic colitis, is epitomized by chronic watery diarrhea, endoscopically normal colonic mucosa, and characteristic histopathological features. Reports on chromoendoscopic findings in microscopic colitis are scarce and in this paper we describe such findings. We have examined 13 patients with microscopic colitis by means of chromoendoscopy with indigo carmine 0.2 % – 0.5 %. In all 13 cases continuous mucosal changes were seen, with disappearance of innominate grooves or with irregularity of grooves. The segmental distribution of abnormal chromoendoscopic findings corresponded almost completely with the microscopic features. A diffuse mosaic pattern was found in five of 10 cases of collagenous colitis and in all three cases of lymphocytic colitis. Uneven surface was seen in four cases of collagenous colitis, one of collagenous colitis in remission, and one of lymphocytic colitis, and a nodular surface was recorded in five cases of collagenous colitis but in none of the lymphocytic colitis cases. If these findings can be reproduced in larger series of microscopic colitis cases, the need for biopsies as a diagnostic tool might be restricted to patients where chromoendoscopy shows clear mucosal changes, thereby saving costs and limiting possible complications associated with multiple biopsies.